PENGUATAN UMKM BERBASIS KUE BASAH UNTUK PENINGKATAN KESEJAHTERAAN MASYARAKAT KAMPUNG BALEKAMBANG SUKARINGIN BEKASI - Miftahussa'adah Wardi; Nopita Sri Mulyani; Sheila Azmi Alifa; Farah Nur Latifah (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
This community service activity aims to improve the welfare of the residents of Kampung Balekambang, Sukaringin Village, Bekasi Regency, through the empowerment of Micro, Small, and Medium Enterprises (UMKM) specializing in traditional snacks (kue basah). The program includes training in innovative kue basah production, mentoring in business management, and developing branding and marketing strategies for the products. Participatory communication processes were conducted using local media, such as WhatsApp groups and regular meetings, to ensure active community involvement. The results show increased production capacity, improved product quality, and a 30% rise in community income. Additionally, the marketing reach of the products expanded to regional levels. This activity demonstrates that strengthening UMKM specializing in kue basah positively impacts not only economic aspects but also social cohesion within the community.